2015
DOI: 10.1016/j.jval.2015.09.739
|View full text |Cite
|
Sign up to set email alerts
|

Economic Analysis Of Evarrest® Sealant Matrix Compared With Standard Of Care In Severe Soft Tissue Surgical Bleeding: A United Kingdom Hospital Perspective

Abstract: unheated CO2 (U-CO2) in laparoscopic patients. Efficacy data were derived from a published randomised controlled trial reporting on the proportion of patients with hypothermia, a US database analysis of hypothermia patients for open surgery, and from an unpublished UK NHS before and after study of laparoscopic surgery patients. Other parameter inputs were obtained from published literature. Deterministic and probabilistic sensitivity analyses were conducted to assess the robustness of results. Scenario analyse… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Cost studies of a novel fibrin sealant matrix, EVARREST, compared to standard of care have shown cost savings for hepatic surgery in a US hospital setting [8] and for soft tissue surgery in Italian, German, and UK hospital settings [69][70][71]. Similarly, a retrospective cost analysis of brain/cerebral surgery, cardiovascular surgery, and carotid endarterectomy using a US hospital database found lower resource utilization and costs associated with the use of SURGICEL advanced products [72].…”
Section: Expert Commentarymentioning
confidence: 99%
“…Cost studies of a novel fibrin sealant matrix, EVARREST, compared to standard of care have shown cost savings for hepatic surgery in a US hospital setting [8] and for soft tissue surgery in Italian, German, and UK hospital settings [69][70][71]. Similarly, a retrospective cost analysis of brain/cerebral surgery, cardiovascular surgery, and carotid endarterectomy using a US hospital database found lower resource utilization and costs associated with the use of SURGICEL advanced products [72].…”
Section: Expert Commentarymentioning
confidence: 99%
“…For example, the use of sutures for wound closure is time-consuming, may cause further tissue damage, may result in infection, and does not provide immediate sealing to prevent leakage of bodily fluids or exposure to air. The application of adhesives is a convenient alternative method for wound closure because of the simple implementation procedure, shorter healing time, less pain for patients, and lack of need for removal 7 . It is extremely challenging to achieve strong adhesion in soft tissues while minimizing toxicity, tissue damage, and other side effects caused by the sealing materials.…”
Section: Introductionmentioning
confidence: 99%
“…14 Although it is accepted that fibrin sealants can be effective as adjunct therapies to achieve hemostasis during liver resections, there seems to be weak evidence on the efficacy of fibrin sealants in reducing the use of blood products, postoperative complications and mortality. 32,33 The cost-savings efficacy of local hemostatic agents has been also object of debate, with reports in favor 34,35 or against. 36…”
Section: Discussionmentioning
confidence: 99%